2015
DOI: 10.1016/j.chemgeo.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Mantle-derived helium in hot springs of the Cordillera Blanca, Peru: Implications for mantle-to-crust fluid transfer in a flat-slab subduction setting

Abstract: Mantle-derived helium in hot springs of the cordillera Blanca, Peru: Implications for mantle-to-crust fluid transfer in a flat-slab subduction setting, ABSTRACT Fault-controlled hot springs in the Cordillera Blanca, Peru provide geochemical evidence of mantle-derived fluids in a modern flat-slab subduction setting. The Cordillera Blanca is a ~200 km-long mountain range contains the highest peaks in the Peruvian Andes, located in an amagmatic reach of the Andean arc. The Cordillera Blanca detachment defines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 61 publications
(99 reference statements)
7
39
0
Order By: Relevance
“…The Cordillera Blanca is a massif in the Peruvian flat slab segment (a distinct type of low-angle subduction 47 ) characterized by an absence of active continental arc magmatism and a millions years old undertaking extensional regime 48 . The helium isotopic data from the thermal springs issuing from this region provided direct evidence for circulation of mantle-derived fluids in an amagmatic flat-slab setting 49 . The more southern Pampean flat-slab segment of the Central Andes displays a similar scenario of the Cordillera Blanca, but with minor current extensional tectonics 50 and known degassing activity 15 .…”
Section: Resultsmentioning
confidence: 88%
“…The Cordillera Blanca is a massif in the Peruvian flat slab segment (a distinct type of low-angle subduction 47 ) characterized by an absence of active continental arc magmatism and a millions years old undertaking extensional regime 48 . The helium isotopic data from the thermal springs issuing from this region provided direct evidence for circulation of mantle-derived fluids in an amagmatic flat-slab setting 49 . The more southern Pampean flat-slab segment of the Central Andes displays a similar scenario of the Cordillera Blanca, but with minor current extensional tectonics 50 and known degassing activity 15 .…”
Section: Resultsmentioning
confidence: 88%
“…The hanging wall comprises Jurassic to Cretaceous sediments, Eocene-Pliocene volcanics, and Miocene-Pliocene sediments of the Lloclla Formation (Cobbing et al, 1981;Petford and Atherton, 1992;Giovanni et al, 2010;Margirier et al, 2015). Hot springs issue along the main detachment system and along steeply dipping faults and inferred synthetic faults proximal to the shear zone (Newell et al, 2015). We present data from samples collected in Quebrada Gatay (Fig.…”
Section: ■ Geologic Background and Sample Descriptionsmentioning
confidence: 98%
“…A trend in increasing CO2/ 3 He ratios is therefore commonly associated with admixture of crustal CO2 and/or degassing in open system (e.g. Crossey et al, 2009;Newell et al, 2015;Ruzié et al, 2013), defined by Rayleigh fractionation. Here, we test both of these possibilities.…”
Section: Radiogenic 4 He Stripping From Enriched Pore-watermentioning
confidence: 99%
“…CO2/ 3 He ratios ranging between 10 9 to 10 14 combined with δ 13 C(CO2) values without an obvious trend towards organic of carbonate end-member is a common observation, commonly interpreted as a result of simple mantle and crustal end-member mixing (Aka et al, 2001;Crossey et al, 2009;Mao et al, 2009). Other workers recognised that simple mixing is not a conclusive interpretation (Italiano et al, 2014) and suggested contribution of a solubility fractionation process (Matthews et al, 1987;Hilton, 2009;Newell et al, 2015). Where open system Rayleigh fractionation is proposed, it is commonly not conclusively supported by evidence from δ 13 C(CO2) values (Ruzié et al, 2013;Bräuer et al, 2016).…”
Section: Radiogenic 4 He Stripping From Enriched Pore-watermentioning
confidence: 99%
See 1 more Smart Citation